Cybernetics of practice. Issue 8 (7th September 2015) - Sweeting, Ben
Abstract : Purpose: – The purpose of this paper is to explore ways in which cybernetics leads to distinctiveways of acting. Design/methodology/approach: – Paralleling von Foerster's argument that it makes more sense to speak of the cybernetics of epistemology than the epistemology of cybernetics, the author argues that cybernetics is not one form of practice amongst others but an account of what it is to practice, understood as where we relate how we act to how we understand so that each informs the other. The author explores the potential difference that adopting this understanding of practice makes in practice and shows its significance by establishing connections between the eponymous cybernetic example of steering and questions regarding teleology in ethics. Findings: – While all practice is cybernetic in the sense of involving a relationship between understanding and acting, the relationship between cybernetics and practice is not a neutral one. Understanding practice in cybernetic terms enables us to pursue goods internal to the practice, which, in turn, makes a difference to how we act. Practical implications: – The author argues that how we understand the relation between our understanding and our acting (our theories of theory and practice) leads to significant differences of action in practice. Originality/value: – The author argues that cybernetics has non-neutral, and ethically significant, consequences in practice that are beyond the application of cybernetics to practice or the advantages of adopting explicitly conversational ways of acting.